The Fyn-STAT5 Pathway: A New Frontier in IgE- and IgG-Mediated Mast Cell Signaling - Pullen, Nicholas A.; Falanga, Yves T.; Morales, Johanna K.; Ryan, John J. (Frontiers in Immunology, 2012)
Mast cells are central players in immune surveillance and activation, positioned at the host-environment interface. Understanding the signaling events controlling mast cell function, especially those that maintain host homeostasis, is an important and still less understood area of mast cell-mediated disease. With respect to allergic disease, it is well established that IgE and its high affinity receptor FcεRI are major mediators of mast cell activation. However, IgG-mediated signals can also modulate mast cell activities. Signals elicited by IgG binding to its cognate receptors (FcγR) are the basis for autoimmune disorders such as lupus and rheumatoid arthritis. Using knowledge of IgE-mediated mast cell signaling, recent work has begun to illuminate potential overlap between FcεRI and FcγR signal transduction. Herein we review the importance of Src family kinases in FcεRI and FcγR signaling, the role of the transcription factor STAT5, and impingement of the regulatory cytokines IL-4, IL-10, and TGFβ1 upon this network.